“Estrategias de marketing para incremento de las ventas en la microempresa Postres Valencia Provincia los Ríos año 2022”. - Macias Vélez, Angie Yulissa (2023)
This research work entitled "MARKETING STRATEGIES FOR THE INCREASE OF SALES IN THE MICRO-ENTREPRISES DESSERT IN VALENCIA LOS RÍOS PROVINCE YEAR 2022" in order to establish marketing strategies to encourage the increase of sales of the micro-enterprise of desserts in Valencia. For this purpose, bibliographic research was developed for the collection of information on the variables of the study, field research for the application of the survey, descriptive research to describe the characteristics of the problem investigated, the research methods used, and the deductive and analytical methods. The research techniques used were the interview applied to the owner and the survey applied to the population, the main instrument being the questionnaire. The population consisted of the inhabitants of the canton of Valencia and the sample was 397 once the sampling formula was applied. It is concluded that the implementation of promotional strategies has played an important role to publicize the new products to be offered by the bakery, through advertising campaigns in local media, and social networks generating a high level of visibility and brand awareness. This has led to a significant increase in awareness and demand for the new flavors, as well as increased traffic to the store and an increase in sales. It is recommended to continue innovating and developing new dessert flavors to keep the offer fresh and attractive, as well as to continue conducting market research to identify current preferences and trends.